Influence of image filters on the reproducibility of measurements of alveolar bone loss - Alves, Wivian Eiras Garcia Wong [UNESP]; Ono, Evelise [UNESP]; Tanaka, Jefferson Luis Oshiro [UNESP]; Medici Filho, Edmundo [UNESP]; De Moraes, Luiz César [UNESP]; De Moraes, Mari Eli Leonelli [UNESP]; Castilho, Julio Cezar de Melo [UNESP] (FapUNIFESP (SciELO), 2006)
The reproducibility of measurements of alveolar bone loss on radiographs may be a problem on epidemiologic studies, as they are based on comparisons of the diagnosis of various examiners. The aim of the present research paper was to assess the inter- and intra-examiner reproducibility of measurements of the interproximal alveolar bone loss on non-manipulated digital radiographs and after the application of image filters. Five Oral Radiologists measured the distance between the cementoenamel junction (CEJ) to the alveolar crest or to the deepest point of the bony defect on 12 interproximal digital radiographs of molars and bicuspids of a dry human skull. The digital manipulation and the linear measurements were obtained with the Trophy Windows software (Throphy®). For each image, six different versions were created: 1) non-manipulated; 2) bright-contrast adjustment; 3) negative; 4) negative with brightness-contrast adjustment; 5) pseudo-colored; 6) pseudo-colored with brightness-contrast adjustment. In order to prevent interpretation bias because of the repetition of measurements, the examiners measured the radiographs in a random sequence. The two-way ANOVA test at 5% level of significance to compare the means of readings of the same operator with each filter indicated p<0.05 for the majority of operators, while the comparison between the mean values of operators using the same filter indicated p>0.05 for all filters. Based on the results, we concluded that linear measurements of interproximal alveolar bone loss on digital radiographs are highly reproducible among examiners. Nevertheless, the application of image filters significantly influenced the degree of intra-examiner reproducibility. Some filters even reduced the reproducibility of intra-examiner readings.
Keywords: Digital radiography; Linear measurements; Periodontal disease